2016
DOI: 10.1007/s00405-016-3911-y
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of nasal tip support in primary, open approach septorhinoplasty

Abstract: The reconstruction of the nasal tip support is one of the most essential issues in septorhinoplasty. A comparison of the results after using the tongue-in-groove technique and the columellar strut technique was the target of this study. Thirty-three patients who underwent a primary, open approach septorhinoplasty using the above-mentioned techniques were retrospectively analyzed. The gain in tip rotation postoperatively, the sensitivity and the rigidity of the nasal tip and the aesthetic outcome after surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…29 Because drooping noses are frequent in parts of Europe, such as France, the causes of this may range from environmental variables to the physical appearance of Asians, as shown in the literature. 30 The surgeon on duty's choice of implementation and how the drooping nose presents itself will determine which of the many procedures is used. They need to be experts since the issue might develop with the implants falling out of position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Because drooping noses are frequent in parts of Europe, such as France, the causes of this may range from environmental variables to the physical appearance of Asians, as shown in the literature. 30 The surgeon on duty's choice of implementation and how the drooping nose presents itself will determine which of the many procedures is used. They need to be experts since the issue might develop with the implants falling out of position.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates that drooping noses are less common among residents of Asian-populated regions 29 . Because drooping noses are frequent in parts of Europe, such as France, the causes of this may range from environmental variables to the physical appearance of Asians, as shown in the literature 30 . The surgeon on duty’s choice of implementation and how the drooping nose presents itself will determine which of the many procedures is used.…”
Section: Discussionmentioning
confidence: 99%
“…Karaiskakis et al reported that both tongue-in-groove and columellar strut techniques led to high percentages of tip rigidity, which was based on a questionnaire. 12 Atighechi et al expressed that both tongue-in-groove and columellar strut techniques showed similar tip elasticity measured by an instrument. 13 In the flexible Plastic and Reconstructive Surgery • December 2021 tongue-in-groove technique, we think the zone where the medial crura end and the vestibular skin begins functions as a joint that allows movement of the medial crura, especially in the coronal plane.…”
Section: Plastic and Reconstructive Surgery • December 2021mentioning
confidence: 99%